The Role of Training and Development Programs on Employee Job Satisfaction - Purnomo Adji Churnawan, Rizky (Greenation Publisher & Yayasan Global Research National, 2024)
Industrial training and development has an important role in improving employees' skills, knowledge, and readiness to face challenges in a dynamic work environment. The industrial development process requires support from the work environment to maintain good employee quality and is related to employee job satisfaction. This research explores the important role of training and development in the industrial environment and its impact on employees. This research uses a literature study with a qualitative approach, collecting data from articles, and journals. The results revealed that training and development plays an important role in improving employees' technical and non-technical skills, as well as encouraging their career development. Some of the factors that influence employee satisfaction and dissatisfaction include working conditions, pay, security, and interpersonal relationships. Training and development is identified as a key element to improve individual and organizational performance, as well as ensuring employee satisfaction through empowerment, effective communication, and recognition of their contributions. The implications of this study suggest that investment in employee training and development can provide a competitive advantage and improve overall organizational productivity.